The Politics of Community Relocation: An Eastern Cree Example - Preston, Richard J. (Culture)

(untitled) (Canadian Anthropology Society / Société Canadienne d’Anthropologie (CASCA), formerly/anciennement Canadian Ethnology Society / Société Canadienne d’Ethnologie, 1982)
In the fall of 1977 the Nemaska Band held a meeting with representatives of the Grand Council of the Crees (of Quebec), Peat, Marwick & Partners, Daniel Arbour & Associates, DINA, and some other consultants. The meeting was held at the proposed site for the new Nemaska community, and lasted four days. It began with a bear feast and ended with a community plan. In the five years following, much of the plan has been successfully implemented. This case study contrasts with the more typical studies of failure in planning, or failure in implementation. While the study of a success is no excuse for ignoring problems faced by other prople, the Nemaska case can serve a constructive role in identifying the means to success in dealing with goals, obstacles, strategies, and practical steps for development.